Ekonomi Rumah Tangga Petani : Pola Pertanian Terpadu di Propinsi Riau (Household Economic Farmers: integrated farming in the province of Riau) - Latifa Siswati (Fakultas Pertanian Universitas Tamansiswa Padang, 2012)
This study aims to: 1) Identify the behavior of production, consumption and application of integrated farming technology in households that implement the integration of plantations, crops and cattle in the province of Riau. 2) Provided the identification of resilience and response capacity of households to maintain the sustainability of integrated farming and household needs 3) Knowing the impact of external factors on the economic decisions of farmers farming households integrated farm, crops and cattle according to the farmers in the province of Riau. The model is formulated in this study is the structural equation model simultaneously. The model has 56 equations consisting of 32 structural equations and 24 identities equations. The number of endogenous variables as much as 56 and as many as 51 exogenous variables. Once the model is identified by using the order condition, obtained the whole equation is